2021
DOI: 10.1096/fj.202002452r
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal deletion of Bmal1 in mice protects against obstructive renal fibrosis via suppressing Gli2 transcription

Abstract: Circadian clock is involved in regulating most renal physiological functions, including water and electrolyte balance and blood pressure homeostasis, however, the role of circadian clock in renal pathophysiology remains largely unknown. Here we aimed to investigate the role of Bmal1, a core clock component, in the development of renal fibrosis, the hallmark of pathological features in many renal diseases. The inducible Bmal1 knockout mice (iKO) whose gene deletion occurred in adulthood were used in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
(112 reference statements)
0
17
0
Order By: Relevance
“…On the other hand, upon adenine treatment, Clock mutant mice showed significantly higher BP and worse renal function than control mice, implying the circadian BP disruption enhances the susceptibility to chronic kidney disease [91]. However, our own recent study found that postnatal Bmal1 deletion in mice protected against renal fibrosis via suppressing Gli2 transcription, which provides a prominent role of the core clock gene Bmal1 in tubulointerstitial fibrosis [92]. Nevertheless, more efforts need to be made from different point of view to further clarify the relationship between circadian BP disruption and chronic kidney diseases.…”
Section: Disruption Of Circadian Bp Rhythm and Renal Damagementioning
confidence: 83%
“…On the other hand, upon adenine treatment, Clock mutant mice showed significantly higher BP and worse renal function than control mice, implying the circadian BP disruption enhances the susceptibility to chronic kidney disease [91]. However, our own recent study found that postnatal Bmal1 deletion in mice protected against renal fibrosis via suppressing Gli2 transcription, which provides a prominent role of the core clock gene Bmal1 in tubulointerstitial fibrosis [92]. Nevertheless, more efforts need to be made from different point of view to further clarify the relationship between circadian BP disruption and chronic kidney diseases.…”
Section: Disruption Of Circadian Bp Rhythm and Renal Damagementioning
confidence: 83%
“…BMAL1 is the main transcriptional activator of the circadian clock, which has been shown to regulate the progress of various renal diseases. 7 , 8 , 9 , 10 However, researches on its function in renal IRI are limited. Previous studies have revealed that the expression level of BMAL1 in cardiac and cerebral tissues decreased significantly after IR, 17 , 28 , 29 which is in line with our study showing that renal IR causes a dramatic decrease in BMAL1 expression level in renal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…BMAL1 is the main transcriptional activator of the circadian clock, which has been shown to regulate the progress of various renal diseases 7–10 . However, researches on its function in renal IRI are limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations